2013
DOI: 10.25071/1705-1436.17
|View full text |Cite
|
Sign up to set email alerts
|

Health and Safety for Canadian Youth in Trades

Abstract: This article examines occupational health and safety (OHS), with aparticular focus on youth apprentices. It uses quantitative and qualitativedata to examine the incidence of injuries among youth apprentices, and theirexperiences related to health and safety at work inCanada. Analysis of large-scale national surveys suggests a high incidence ofwork-related injuriesamong youth and low participation rates of youngerworkers in formal OHStraining. A survey of 173 former Ontario Youth Apprenticeship Program(OYAP) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
2
8
0
1
Order By: Relevance
“…In Europe, young workers' risk of accidents at work is 25–40% higher than those of other age groups [2] . These findings are supported by other studies examining occupational health and safety among youths [3–5] .…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…In Europe, young workers' risk of accidents at work is 25–40% higher than those of other age groups [2] . These findings are supported by other studies examining occupational health and safety among youths [3–5] .…”
Section: Introductionsupporting
confidence: 87%
“…The literature also shows that training in occupational safety and health is crucial and must be included in apprenticeship programs to improve the situation. This applies to the form of teaching as well as the content being taught [3,12–14] .…”
Section: Introductionmentioning
confidence: 99%
“…Tucker and Turner (2013) note that young workers in Ontario and Manitoba were generally reluctant to voice concerns about workplace hazards and were unlikely to pursue further remedy if their initial efforts were unsuccessful. This lack of voice is consistent with Raykov and Taylor's (2013) analysis of workplace injury in Alberta and Ontario youth apprenticeship programming.…”
Section: The Employment Of Minors In Canadasupporting
confidence: 76%
“…Alberta (2011a) does provides summary data about lost-time claims and disabling injury claims accepted by the Workers' Compensation Board (WCB) for workers under age 15 and age 15-19, but publishes no data about less severe injuries. Raykov and Taylor (2013) identified that one fifth of Ontario and Alberta participants in youth apprenticeship programs suffered serious occupational injuries that required time off of work.…”
Section: The Employment Of Minors In Albertamentioning
confidence: 99%
“…During the training period, students can be exposed to the same occupational risks as workers. Raykov and Taylor (2013) found a high incidence of injuries among youth who had participated in high school apprenticeship programmes in Canada.…”
Section: Introductionmentioning
confidence: 99%